The dynamics of structural change: the European Union's trade with China - Bianka Dettmer; Fredrik Erixon; Andreas Freytag; Pierre-Olivier Legault Tremblay (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Sino-European trade relations have been controversially discussed mainly, if not only, because of the increasing European Union's bilateral trade deficit with China. As from the European perspective trade with China becomes more important, the structural adjustment process of the Chinese economy from inter-ndustry to intra-industry trade is not as intensively discussed. We show how the emergence of China on the world markets has affected European comparative advantages over time. The change in bilateral trade is compared to the overall development of European comparative advantages to highlight the features of the structural change in China. We show that China is increasingly specialising in technology intensive goods. This development is absolutely in accordance with the historical perspective on country's upgrading in technology while integrating into the world economy. Technology intensive Schumpeter goods are either of a mobile or an immobile type based on the selection criterion of separating research and production process. While China predominantly focuses on the mobile type of Schumpeter goods, the European Union maintains its comparative advantages in immobile technology intensive goods, which are harder to imitate. Based on technology intensity, the second issue presented in the paper focuses on the Chinese integration into the world-wide value-added chain, which has been fragmented across borders in recent years. Not least due to increasing FDI, intra-industry trade has become more prevalent in bilateral trade relations with China.
Keywords: F11; F14; 330; Comparative advantage; Intra-industry trade; Fragmentation; EU; China; Internationale Wirtschaftsbeziehungen; Intraindustrieller Handel; Komparativer Kostenvorteil; EU-Staaten; Strukturwandel; Technologie; China